Teaching discriminated social approaches to individuals with Angelman syndrome. Issue 4 (6th August 2015) - Fichtner, Caitlin S.; Tiger, Jeffrey H.
Abstract : Angelman syndrome is a neurogenetic disorder characterized by intellectual and developmental disability. Common behavioral characteristics of this disorder include a heightened interest in social interactions and frequent bids to initiate interaction. These bids can be problematic, for instance, when a child attempts to hug strangers in public places. The current study evaluated a discrimination training program to teach 3 boys with Angelman syndrome to discriminate appropriate from inappropriate times to initiate interactions. During baseline, we alternated periods in which attention was delivered following social initiations on a continuous reinforcement schedule with periods in which initiations were placed on extinction. We then implemented discrimination training by presenting a salient discriminative stimulus, prompting the occurrence of initiations, and providing reinforcement during reinforcement periods and withdrawing the stimulus during extinction periods. This resulted in discriminated approaches for each of the 3 participants; these results were replicated across caregivers and extended to the participants' homes.